Interleukin-10 Mitigates Doxorubicin-Induced Endoplasmic Reticulum Stress as Well as Cardiomyopathy - Akshi Malik; Ashim K. Bagchi; Davinder S. Jassal; Pawan K. Singal (Biomedicines, 2022)
The use of doxorubicin (Dox) in cancer patients carries the risk of cardiotoxicity via an increase in oxidative stress, mitochondrial dysfunction, and disturbed endoplasmic reticulum (ER) homeostasis in cardiomyocytes. The present study explores which of the ER transmembrane sensors is involved in Dox-induced apoptosis and whether interleukin-10 (IL-10) has any mitigating effect. There was a time-related increase in apoptosis in cardiomyocytes exposed to 5.43 µg/mL Dox for 0 to 48 h. Dox treatment for 24 h significantly upregulated glucose-regulated proteins 78 and 94, protein disulfide isomerase, cleavage of activating transcription factor 6α, and X-box binding protein 1. These Dox-induced changes in ER stress proteins as well as apoptosis were blunted by IL-10 (10 ng/mL). In Dox-exposed cardiomyocytes, IL-10 also promoted expression of protein kinase-like endoplasmic reticulum kinase and inositol-requiring kinase 1α, which helped in maintaining ER homeostasis. Additionally, under Dox-treatment, IL-10 downregulated caspase-12 activation as well as phosphorylation of c-JUN NH2-terminal kinase, thereby promoting cardiomyocyte survival. IL-10 was able to reduce the overexpression of mitochondrial apoptotic proteins caspase-3 as well as Bax, which were upregulated upon Dox treatment. Thus, a reduction in Dox-induced ER stress as well as apoptosis through IL-10 may provide a significant benefit in improving cardiac function.